2020
DOI: 10.1186/s12884-020-2781-x
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the factors influencing recruitment to a pilot trial on the prevention of striae gravidarum

Abstract: Background: Striae gravidarum are a common occurrence in pregnancy and many women use a topical product to prevent their development or lessen their appearance if they do develop. There is a lack of evidence on the effectiveness of many of the products used by women. This study arose from challenges in recruitment to a pilot randomised trial (ISRCTN trial registration number:76992326) designed to evaluate the feasibility of a definitive trial to compare a moisturising oil to no treatment in the prevention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(109 reference statements)
0
3
0
1
Order By: Relevance
“…The striae gravidarum presents as irregular purple or light red parallel and slightly concave expansion stripes in abdominal skin, and gradually fading into silver bright stripes [ 3 ]. Striae gravidarum brings both psychological burden and mental stress to pregnant women, leading a decrease of their life quality [ 4 ]. The occurrence and treatment have always been a worldwide concern in present medical research [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The striae gravidarum presents as irregular purple or light red parallel and slightly concave expansion stripes in abdominal skin, and gradually fading into silver bright stripes [ 3 ]. Striae gravidarum brings both psychological burden and mental stress to pregnant women, leading a decrease of their life quality [ 4 ]. The occurrence and treatment have always been a worldwide concern in present medical research [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous trials on myo-inositol supplementation in pregnancy reported consent rates over 70% but had a predominantly Caucasian population 15 16. Other pregnancy trials reported similar attrition rates to the EMmY study,15 16 and made reference to phone-based reminders and diaries as crucial to adherence 17 18. The EMmY study was not powered to detect any statistical differences in clinical or laboratory outcomes, including for gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar prompt questions were asked using an interview guide designed and agreed by all authors; additional questions were triggered by responses, and these were permitted as the interview’s policy. [ 17 ] The in-depth interviews also encouraged participants to communicate freely in their style and tempo. [ 18 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%